Network issues in KUKTEM and solutions - Khairul Afham, Sani (2005)
Nowadays,networking has become widespread technology and emerging as one (1) of methods that can connect each of us no matter where you are as long as there has a connection of the network.One (1) way is implementing "Domain" that featured in Windows Server for controlling access of network.Two(2)elements have been identified to take a concern are performance and security.This domain is an alternative way to ease in managing users within an organization.The domain functioned as a controller over the other workstation, which only domain controller will affect through an attack such as viruses that could give benefits to administrator for fixing the problem.The project consists of project requiremnet and analysis design,experiment and testing phase.The project had been implemented using four (4) Pc as a mini-network environment within FSKKP lab.Two(2) domains are created to show that different domain can be connected each another.After several testing,the Domain project are ready to be bring into our real world because it does not neglect the performance and security terms